Adalékok a német "völkisch" történetszemlélet fogadtatásához a Horthy-korszak Magyarországán - Orosz, László (Közép-Európai Közlemények, 2015)
Following her defeat in WWI, within the spirit of a reevaluated “auswärtige Kulturpolitik”, Germany attempted to move closer to the states of our region by using new historiographical tools. Per their “folk6 and cultural soil” reconstruction, the Germans questioned the respective ethnic group’s nationstate6related historical conceptions and emphasized their own revisionist needs. In other words, a “popularist war” replaced the earlier interstate diplomacy even within academia. Hungary – like the other states of the region – felt threatened by Germany within the sphere of scientific policy. Therefore, decisive resistance was witnessed. Beyond these feelings of threat, this counteraction was also motivated by the fact that the German “cultural slide” theory sharply contradicted contemporary Hungarian founding ideology, the Hungarians’ sense of historical mission and their leadership role within the Carpathian Basin, as well as their desire to prove a cultural supremacist theory contra their neighboring peoples. The Hungarians’ more6or6less unanimous dismissal is also proof that the Hungarian historiography of the period was capable of overcoming its own – indeed huge – inner divisions and showing a united front to defend Hungarian interests against these offensive manifestations.